2017
DOI: 10.17356/ieejsp.v3i1.299
|View full text |Cite
|
Sign up to set email alerts
|

Youth, Precarious Employment and Political Participation in Hungary

Abstract: Intersections. EEJSP 3(1): 120-146. DOI: 10.17356/ieejsp.v3i1.299 http://intersections.tk.mta.hu AbstractYoung Europeans' political responses to the economic crisis have neither been uniform nor overly promising for the future of democratic Europe. We seek to identify potential causal relationships between young peoples' employment status and choice of political participation (i.e. both traditional and non-traditional forms of political participation, as well as emerging alternatives). Although politicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…This can affect young women's participation by enabling or limiting their chances depending on how various groups perceive. These findings relate with those of Robert et al, who noted that various levels of employment affect participation of young people in politics [28].…”
Section: Respondent's Employment Statussupporting
confidence: 89%
“…This can affect young women's participation by enabling or limiting their chances depending on how various groups perceive. These findings relate with those of Robert et al, who noted that various levels of employment affect participation of young people in politics [28].…”
Section: Respondent's Employment Statussupporting
confidence: 89%
“…However, the least prevalent are in agriculture (14 %) and education (11 %), which can be considered the most "open" fields. Students form a caste social structure, which is also reflected in unequal access to types of education (Róbert et al, 2017). The results of our study confirm the literature, as we found significant differences when we looked at the internal stratification of higher education by field of study.…”
Section: Social Status Of Studentssupporting
confidence: 88%
“…Children from graduate families were under-represented in the lower-earning education groups, with children of mothers with secondary education and fathers with primary education standing out. An explanation is that the group was dominated by teacher training, which may function as a one-step channel of social mobility (Róbert et al, 2017). Furthermore, in the lower tercile, the majority of parents worked, but women were overrepresented among public workers.…”
Section: Discussionmentioning
confidence: 99%
“…Classified by self-report into 8 mutually exclusive categories and analysis conducted on four groups: permanent full-time, permanent part-time, casual full time, and casual part-time (38). b. Part-time work: working <35 hours per week =1 vs. full-time work=0 (56). Multiple jobs/sectors (30,32,33,46) a.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…The studies investigating contractual temporariness focused on whether the person was employed on a fixed term contract or a permanent contract (25,26,29,30,39,40,47,48,52,53,56,57,82,100). There was substantial heterogeneity in how these two concepts were defined.…”
Section: Included Dimensionsmentioning
confidence: 99%